Interferensi Sintaksis Bahasa Indonesia dalam Skripsi Bahasa Arab Sebagai Upaya Pemetaan Kesalahan Berbahasa Mahasiswa Pendidikan Bahasa Arab - Zuhriyah, Isniyatun Niswah Muflihatuz (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2025)
This study aims to analyze grammatical interference from Indonesian in Arabic language theses written by students of the Arabic Language Education (PBA) program at Universitas Hasyim Asy’ari (UNHASY) Jombang. Interference occurs when Indonesian grammatical patterns influence the use of Arabic, leading to errors in sentence structure and the application of grammatical rules. This research employs a descriptive qualitative method to describe the forms of interference and map out common language errors. The data were collected from theses written by students from the 2020–2023 cohorts using a random sampling technique. Data collection was carried out through the uninvolved conversational observation and note-taking technique, followed by in-depth analysis. The findings indicate that interference occurs at the syntactic and morphological levels, including errors in sentence structure, the use of particles and prepositions, and inaccuracies in selecting plural, singular, and verb forms. The primary factor causing this interference is the application of Indonesian grammatical patterns that do not align with Arabic rules. These findings serve as a basis for mapping linguistic errors and can be used as a reference to enhance Arabic language teaching strategies. With a better understanding of interference patterns, it is hoped that lecturers and educators can develop more contextual and effective teaching materials. This study is expected to contribute to improving the linguistic competence of PBA students in writing academic texts in Arabic. Keywords: grammatical interference, Indonesian language, Arabic language, language errors, student thesese.